TREE SPECIES DIVERSITY AND MANAGEMENT IN AGROFORESTRY POHPOHAN (Pilea melastomoides): THE CASE IN THE TRADITIONAL ZONE OF GUNUNG HALIMUN SALAK NATIONAL PARK, INDONESIA - Adisti Permatasari; Sheikha Ananda Mosa; Bayu Winata; Lufthi Rusniarsyah; Peniwidiyanti Peniwidiyanti; Izzbilhaq Izzbilhaq (BIOTROPIA, 2024)
Article Highlights- Pohpohan (Pilea melastomoides) is the main commodity cultivated by using traditional agroforestry in the traditional zone of Gunung Halimun Salak National Park as a fresh vegetable.- There is a limited database of plant species diversity in the traditional zones, which is dynamic and needs further research.- This study found 54 tree species from 37 families with the dominant family being Rubiaceae.- Most farmers cultivated Pohpohan by conducting plant spacing, maintenance, and harvesting. Their income is USD 154 – 256/month. AbstractGunung Halimun Salak National Park (GHSNP) is Java's largest tropical mountain forest. GHSNP is still facilitating community grounds around GHSNP with the existence of a traditional zone. Pohpohan (Pilea melastomoides) is the primary commodity in the traditional zone cultivated by the local people around GHSNP. Pohpohan is planted using traditional agroforestry planting patterns. The traditional zone has a limited plant species diversity and management database, so further study is necessary. This study was conducted in the traditional zone of GHSNP, specifically at the agroforestry system in Tamansari Village, Bogor Regency. Data collection of tree diversity was conducted by establishing 25 plots. This study also interviewed 30 local farmers belonging to the Mandiri farmer group. There are 54 species from 37 families. Rubiaceae, Malvaceae, Fabaceae, and Phyllanthaceae families are the most common families. Pinus merkusii, Agathis dammara, and Maesopsis eminii have the highest important value index (IVI) values. Understorey and seedlings have a low category on H' due to the dominant planting of Pohpohan. Most respondents are people aged 35-55 (70%) with a farming area of 1000 m2. They cultivate Pohpohan by conducting plant spacing, plant maintenance (e.g., soil cultivation, weeding, fertilization), and harvesting. Most farmers conduct fertilization 9 times/year. Farmers produce 30.000-50.000 bunches/harvest. The price of a bunch of Pohpohan is 0,00054 USD. Their income is about 154 USD – 256 USD/month.